EDUKASI DAN AKSI BERSIH PANTAI GONDOL: UPAYA PENGEMBANGAN MINA WISATA BERKELANJUTAN DI DESA PENYABANGAN, BALI - Mukhlis, Alis (Program Studi Budidaya Perairan Universitas Mataram, 2025)
Penyabangan Village, particularly the Gondol Beach area, possesses significant potential for developing marine tourism that integrates fishery activities with maritime tourism. However, marine debris poses a serious challenge that could threaten the sustainable development of this area. Educational programs and beach cleaning actions were implemented as efforts to raise public awareness about the importance of maintaining coastal environmental cleanliness in supporting sustainable marine tourism development. This activity is a collaboration between the Community Service Program team from the University of Mataram and the Marine Aquaculture, Fisheries and Extension Research Center (BBRBLPP) Gondol, conducted on November 13, 2024. The program adopted a participatory approach through three stages: preparation, education, and beach cleaning action. The results showed an increase in public awareness, reflected in the high participation in beach cleaning activities and the formation of local initiatives to maintain beach cleanliness sustainably. The success of this program provides a foundation for developing the concept of marine tourism that integrates aquaculture potential with maritime tourism, while supporting the economic diversification of coastal communities through the sustainable tourism sector.